Climate variability and change in Ecuador: dynamic downscaling of regional projections with RegCM4 and HadGEM2-ES for informed adaptation strategies - Portalanza, Diego; Torres, Malena; Rosso, Flavia; Zuluaga, Cristian Felipe; Durigon, Angelica; Horgan, Finbarr G.; Alava, Eduardo; Ferraz, Simone (Frontiers in Climate, 2024)
Ecuador, a country with distinct coastal (CO), highland (HL) and Amazon (AM) regions that are characterized by unique climatic, ecological, and socio-economic features is highly vulnerable to climate change. This study focuses on these three regions, highlighting their individual importance in the broader context of Ecuador's climate vulnerability. Utilizing dynamically downscaled data from the Regional Climate Model (RCM), we generated precipitation and air temperature 1 Portalanza et al.projections for the period 2070-2099 under three different climate change scenarios. We indicate projected temperature increases across all three regions: mean temperature increases for the CO, HL and AM regions are of 1.35, 1.55 and 1.21°C, respectively. Each year, the largest temperature increases are predicted for the third quarter (June-August), with the smallest increases predicted for the last quarter (December-February). Precipitation patterns show varied changes, with CO exhibiting a positive mean daily change, in contrast to a mean negative change in the AM region. These region-specific projections underscore the differential impacts of climate change within Ecuador and highlight the necessity for tailored adaptation measures. The study's novel approach, focusing on distinct regional impacts within a single nation, offers valuable insights for policymakers, aiding in the development of effective, region-specific climate change mitigation and adaptation strategies. This targeted approach is crucial to address unique challenges faced by different regions, thereby supporting national resilience strategies.